2014
DOI: 10.1007/s10551-014-2293-6
|View full text |Cite
|
Sign up to set email alerts
|

Are There Gender Differences When Professional Accountants Evaluate Moral Intensity for Earnings Management?

Abstract: Gender differences in ethical evaluations may vary across types of behaviors. This controlled experiment explores gender differences in ethical evaluations, moral judgment, moral intentions, and moral intensity evaluations by surveying a group of professional accountants to elicit their views on a common earnings management technique. We find that there are no significant differences between male and female professional accountants when they make an ethical evaluation involving earnings management by shipping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…The results indicated that both male or female accountants have the same view that earnings management should not be done, and both intend to report if they find evidence of earnings management. Thus the results of the Manafe (2015) and Shawver and Clements (2014) studies support the results of this study.…”
Section: The Relationship Between Gender and Students' Perceptions Ofsupporting
confidence: 88%
“…The results indicated that both male or female accountants have the same view that earnings management should not be done, and both intend to report if they find evidence of earnings management. Thus the results of the Manafe (2015) and Shawver and Clements (2014) studies support the results of this study.…”
Section: The Relationship Between Gender and Students' Perceptions Ofsupporting
confidence: 88%
“…Such helping behaviors benefit both the targets (coworkers) and the employees themselves, because they not only enhance coworkers' ability to meet their performance targets marked by the reduce-depleting leadership style of despotic leadership (Hobfoll and Shirom, 2000). Finally, consistent with social role theory (Eagly, 1987), this triggering effect of despotic leadership may be especially forceful among female employees, because of their typically more caring and nurturing nature (Eagly and Crowley, 1986;Shawver and Clements, 2015).…”
Section: Introductionmentioning
confidence: 66%
“…For the purpose of this study, a laboratory experiment was developed in order to test the research hypotheses above using students as participants. Despite the limits involved when using students as substitutes of managers, previous empirical studies assessing earnings management used this path (Greenfield et al, 2008;Shawver and Clements, 2014). The experiment was conducted in two steps.…”
Section: Methodsmentioning
confidence: 99%